Primary care in London: an evaluation of general practitioners working in an inner city accident and emergency department. Issue 1 (January 1996) - Ward, P; Huddy, J; Hargreaves, S; Touquet, R; Hurley, J; Fothergill, J
Abstract : OBJECTIVE: To determine the characteristics of primary care attenders to St Mary's Hospital accident and emergency (A&E) department, evaluate the effects of the introduction of general practitioners (GPs) on patient care in A&E, and make recommendations for the provision of GPs in appropriate A&E departments. DESIGN: Prospective survey over a six week period. METHODS: Data collected from the attendances of 970 consecutive patients triaged with "minor" primary care problems, whether seen by A&E doctors or by GPs working in A&E, were analysed. RESULTS: During the study period 1078 patients (16.6%) were triaged as suitable for primary care. The A&E GPs saw 58.4% of these patients. The majority of primary care patients were young British residents, 71.1% of whom were registered with a GP. Sixty per cent of patients lived within St Mary's catchment area. Of those registered patients asked why they attended A&E, 27.1% thought their problem inappropriate for their GP. A&E doctors were more likely to investigate patients and arrange hospital follow up than GPs, who arranged community follow up in 80% of patients needing further care. CONCLUSIONS: The demand for primary care at St Mary's necessitates the provision of a primary care service, albeit for the first visit only. This can be provided by GPs in A&E. The features of the patients using the service suggests that discouraging first attendance is unrealistic, but using the visit to educate patients and return them to the care of the community is not.